PENGARUH JENIS PELARUT TERHADAP KLOROFIL DAN SENYAWA FITOKIMIA DAUN KIAMBANG (Salvinia molesta Mitchell) DARI PERAIRAN RAWA UNSRI - Yaya Ernaini; Agus Supriadi; Rinto Rinto (Universitas Sriwijaya, 2012)
The objective of this research was to know effect of solvent (NaHCO3 0,5% and MgCO3 0,03%) and Tween 80 (0,5%, 1%, and 1,5%) to obtain the chlorophyll and phytochemical compounds of kiambang leaves. The research used factorial randomized block design with two treatments and each treatment was replicated three times. The treatments wereÂ the type of solvent (NaHCO3 0.5% and MgCO3 0.03%) and the concentration of Tween 80 (0.5%, 1% and 1.5%). The parameters of research were total chlorophyll content, water dissolve chlorophyll, phytochemichal, colour intensity (Hunter a, Hunter b, and Lightness), and colour stability. The result showed that the average of total chlorophyll ranges from 10.261 mg/L to 16.435 mg/L, water dissolve chlorophyll ranges from 4.503 mg/L to 5.739 mg/L, Hunter a ranges from -2.8 to -4.667, Hunter b ranges from +6.1 to +14.6, Lightness ranges from 29.4 to 34.067. Phytochemical compounds of kiambang leaves were alkaloid, fenol, and saponin. The colour stability test of kiambang leaves by using NaHCO3 0.5% and Tween 80 1.5% indicated the best colour stability during four weeks storage in aerobic condition. Â Keyword: kiambang extract, chlorophyll, phytochemical